2014
DOI: 10.1093/gerona/glu204
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Disability in Activities of Daily Living Among Chinese Older Adults, 1997–2006: The China Health and Nutrition Survey

Abstract: The prevalence of disability in basic ADLs among Chinese older adults decreased from 1997 to 2006. Stroke and multiple cardiometabolic diseases appear to become less disabling over time, which may partly contribute to the favorable trend in ADL disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 27 publications
9
54
1
Order By: Relevance
“…This study supports the idea that the decreasing prevalence of ADL disability in Chinese older adults, as previously reported, might be partly attributed to the declining incidence of disability. Furthermore, previous research has revealed a pattern of functional decline and recovery in ADL in older adults, and the transition from ADL‐disabled condition to active status is nontrivial .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study supports the idea that the decreasing prevalence of ADL disability in Chinese older adults, as previously reported, might be partly attributed to the declining incidence of disability. Furthermore, previous research has revealed a pattern of functional decline and recovery in ADL in older adults, and the transition from ADL‐disabled condition to active status is nontrivial .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported a different prevalence of ADL disability between urban and rural areas in China, although the rural–urban difference tends to diminish over time . Similarly, the current study found that the incidence of ADL disability was generally comparable in rural and urban residents in the three cohorts, although the decline in incident disability was more evident in rural residents.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The first is the mixed effects of the two opposing processes of the “compression of morbidity (benefits of success)” and “expansion of morbidity (costs of success)”. On one hand, the later cohorts might benefit from progress resulted from more effective disease treatment, healthier lifestyles, declining disability effects of some major chronic diseases such as stroke and cardio-metabolic disease, 15 and improved standards of living, due to rapid socioeconomic development in China. This “benefits of success” implied that the later oldest-old cohort experienced reduced mortality rates by postponement of senescence, and reached older ages with improved health and functional capacity in daily living.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, Wu et al concluded that dementia prevalence among elderly aged 70+ was in general increasing, based on an evaluation of seventy prevalence studies of dementia in Mainland China, Hong Kong and Taiwan from 1980 to 2012. 17 Similarly, Chan et al found that the prevalence of all forms of dementia at ages 65–69 and 95–99 in China in 2010 increased 44.4% and 43.7%, respectively, compared to 1990.…”
Section: Introductionmentioning
confidence: 99%